2017
DOI: 10.1159/000458411
|View full text |Cite
|
Sign up to set email alerts
|

Is Periodontal Disease Associated with Alzheimer's Disease? A Systematic Review with Meta-Analysis

Abstract: Background: In the last decade, several observational studies have suggested that there exists an association between periodontal disease (PD) and Alzheimer's disease (AD). The aim of this systematic review was to investigate whether or not this link exists. Summary: The Preferred Reporting Items for Systematic Reviews and Meta-Analysis guideline for systematic review was used and registered at PROSPERO (CRD42016035377). The search strategy included using electronic databases and by hand searching articles pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
82
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 45 publications
1
82
0
6
Order By: Relevance
“…ApoE fragmentation has been extensively studied in relation to Alzheimer's disease; therefore, it could be worth mentioning that P. gingivalis has been shown to be able to invade the brain, and possibly the gingipain‐induced proteolysis of lipoproteins may be a mechanism involved in the local atherogenic process and in the degenerating brain as well. Furthermore, several studies have reported a link between periodontitis and Alzheimer's disease …”
Section: Discussionmentioning
confidence: 99%
“…ApoE fragmentation has been extensively studied in relation to Alzheimer's disease; therefore, it could be worth mentioning that P. gingivalis has been shown to be able to invade the brain, and possibly the gingipain‐induced proteolysis of lipoproteins may be a mechanism involved in the local atherogenic process and in the degenerating brain as well. Furthermore, several studies have reported a link between periodontitis and Alzheimer's disease …”
Section: Discussionmentioning
confidence: 99%
“…tooth loss) have been associated with cognitive decline/impairment in patients with AD (Holmer, Eriksdotter, Schultzberg, Pussinen, & Buhlin, ; Ide et al, ; Takeuchi et al, ). A recent meta‐analysis of observational studies showed that subjects diagnosed with periodontitis have a 1.6‐fold increased risk of developing AD (Leira et al, ). We recently demonstrated that bacterial endotoxin (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews suggest that older people with dementia have multiple oral health problems (Delwel et al, 2018;Gusman et al, 2018;Leira et al, 2017;Maldonado, Laugisch, Burgin, Sculean, & Eick, 2018). However, studies on the relationship between periodontitis and cognitive decline are few but indicate an association (Gil-Montoya et al, 2014;Syrjala et al, 2012;Zenthofer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%